Analysis of digital terrestrial television development in Taiwan - KuangChiu Huang; Mei-han Liao (International Telecommunications Society (ITS), 2012)
The development of digital terrestrial television (DTT) plays an important role of digital convergence. However, a regulator need not only select a suitable DVB standard but also decide timing of transition between existing standard and new standard. Although there are four major standards of digital terrestrial television in the world (ATCS, DVB-T, ISDB, DTMB), Taiwan, without its own standard, requires careful study to choose a suitable standard to enable digital convergence. According to the digitalization development and the technology evolution, the national communication commission (NCC) adopts a popular European standard, digital video broadcast-terrestrial (DVB-T) established by European Broadcast Union (EBU) in 1997, to develop its digital television systems.
Keywords: 330; DTT; DVB-T; DVB-T2; ICT; benchmarking; stakeholder analysis